Arqueología de la Edad Moderna en el País Vasco y su entorno - Sologestoa, Idoia Grau; Quirós Castillo, Juan Antonio (Access archaeology., 2020)
Post-medieval archaeology is currently going through a critical phase of consolidation and disciplinary redefinition across Europe, where mere proposals or ambitions are becoming tangible scientific and disciplinary realities. This renovation is most evident in Southern Europe, where, until recently, these studies have been treated as somewhat marginal. The convergence of new actors and disciplines, the promotion of new patrimonialisation initiatives, and the creation of new action frameworks as a result of the deep economic crisis of the years 2007-2008 are some of the factors that have shaped current approaches to the archaeology of the Modern Age. Focusing on archaeological studies of the Modern Age located in the Basque Country, this book recognises the main themes investigated, detects some of the strengths and weaknesses, and proposes new lines of action and disciplinary consolidation.